Gendered resilience in India’s seaweed farming: Highlighting policy lessons from the COVID-19 pandemic for inclusive Blue economy framework - Sundaram Swathi Lekshmi Perumal; Radhakrishnan Kalidoss; Gopal Nikita; D. Divu; Mojjada Suresh Kumar; V.P. Vipin Kumar; George Saju; S. Surya; R. Narayanakumar; Kingsly Jose; V.A. Leslie; S.S. Arabindoo; et al. (Marine Policy, 2026)

Ecosystem spectral fingerprinting and geospatial evaluation of hydrological and vegetation dynamic processes in the Bhavani River Basin, Southern India - S. Zuvairiya; S.R. Singarasubramanian; A. Bobby Jones; V. Gopal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Multi-trait model-based assessment of selection efficiency and stability in soybean germplasm - Sachin Munde; Gopal Wasudeo Narkhede; Gali Suresh; Sandeep Shinde; Padmakar Wadikar; Ambika More; Hirakant Kalpande; K S Baig; Shivaji Mehtre (Journal of Applied Genetics, 2026)

Mimosa pudica Linn. - An important medicinal plant: Pharmacognostic evaluation, bioactive compound isolation, structural elucidation, and in silico analysis - Kousik Ghosh; Karthick Gopal; Lakshmanan Narayanan; Vamsee Krishna K․; Akansha Pandey; Aswathi Mohan P․; Siva Surya; Suseem S R; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Distribution and Ecological Risk of Microplastics Across Air, Water, and Soil in a Coastal Megacity of Southern India - M. Bhuvaneswari; Anju Maria Joseph; S. Yamini; M. Suresh Gandhi; V. Gopal (Water, Air, & Soil Pollution, 2026)

Integrated Transcriptomic and Small RNA Profiling Reveals Regulatory Networks Associated With Seed Protein Accumulation in Chickpea (Cicer arietinum L.) - Gopal Kalwan; Deshika Kohli; Yashwant Kumar Yadava; Sheel Yadav; Suruchi Khanna; Ila Joshi; MS Nimmy; S. V. Amitha Mithra; Biswajit Mondal; Shailesh Tripathi; Satvir Kaur Grewal; Kishor Gaikwad; et al. (Journal of Plant Growth Regulation, 2026)

Elucidating the molecular basis of Streptomyces antifungal activity against Fusarium verticillioides, causing maize ear and stalk rot pathogen - K.N. Pallavi; M.K. PrasannaKumar; J. Harish; R. Karan; Gopal Venkateshbabu; M. Nithish; C. Manjunatha; Deepaka; Swathi S. Patil; Aditya Narayan Sarangi (Biocatalysis and Agricultural Biotechnology, 2026)

Integrated experimental, statistical, and ANN validation study on concrete deterioration under acid rain, carbonation, and chloride environments - Y. H. Sudeep; V. Vijaykumar; M. S. Ujawl; Christo George; S. Karthik; Rakesh Kumar; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2026)
Concrete structures in coastal–industrial regions are simultaneously exposed to acid rain, carbonation, and chloride ingress; however, most durability studies investigate these mechanisms independently, limiting realistic service-life prediction. This study presents an integrated experimental, statistical, and artificial neural network (ANN)-based evaluation of M40-grade concrete subjected to synthetic acid rain, accelerated carbonation, and combined carbonation–chloride environments. Laboratory simulations were conducted for exposure durations of 20, 40, 60, and 80 h to replicate aggressive atmospheric conditions. Mechanical degradation was assessed through compressive and splitting tensile strength tests, while chemical deterioration was quantified using depth-wise pH profiling and carbonation depth measurements. Results revealed that compressive strength decreased by up to ~ 25% under acid rain exposure and showed greater deterioration under combined carbonation–chloride conditions. Splitting tensile strength exhibited higher sensitivity to degradation, with reductions exceeding 20% at prolonged exposure durations. Surface pH declined from 12.6 to approximately 8.8, confirming rapid alkalinity loss in the outer 1 cm zone. Carbonation depth increased progressively, reaching ~ 11.5 mm in the combined exposure environment. Regression analysis demonstrated strong inverse correlations (R 2 > 0.90) between carbonation depth and mechanical properties, while one-way ANOVA confirmed statistically significant differences across exposure durations ( p < 0.05). To enhance predictive capability, an ANN model was developed using experimental parameters as inputs, achieving high prediction accuracy (R 2 = 0.98 for training and R 2 = 0.96 for testing). The findings highlight synergistic deterioration effects of multi-environmental exposure and emphasize durability-based design strategies for reinforced concrete structures in aggressive environments.

Effect of cuttings length and propagation method on rooting efficiency of exotic clonal rootstocks of apple (Malus × domestica Borkh.) - Sanjana Singh; Gopal Singh; Vishal S. Rana; Diksha Dhiman; Neerja Rana; Ruchi Kumari (Agricultural Research, 2026)

Molecular insights into fibromyalgia: association of hub genes with pain targets, neuropathic pathways, and stress-related hormones - K. Gowri Gopal; Linda S Robi; D. R. Sherin (In Silico Pharmacology, 2026)

Radon-thoron exhalation rates in mineral-enriched beach sand of the Chennai coast, India - M. John Samson; K. Manikanda Bharath; A. Vidyasakar; K. Ajith Kumar; V. Arun Bharathi; Satyanarayan Bramha; S. Chandrasekaran; Kannaiyan Neelavannan; V. Gopal; S. Ajith Kumar; N. Sivakumar (Environmental Geochemistry and Health, 2026)

Role of mesoscale eddy on the occurrence of a rare polychaete swarm after five decades in Bay of Bengal waters, northern Indian Ocean - Aiswarya Gopal; Manigandan V.; Sathishkumar R. S.; Logesh Natarajan; Sanitha K. Sivadas; Karri Ramu; R. S. Kankara (Marine Biodiversity, 2026)

The in vitro and in silico investigations on the α-amylase inhibitor derived from Leptadenia lanceolata (Poir.) Goyder leaf extract - Salman Abubakar Adam; Infant Santhose Barthelomai; Subhash Bharathi S; Alaa Kayali; Rajesh Kanna Gopal (Natural Product Research, 2026)

A hybrid deep learning based framework for prediction of rice yield through integration of biophysical parameters and optical remote sensing data in India - Rafath Samrin; Pundru Chandra Shaker Reddy; K. Arun Kumar; Natha Deepthi; C. Mithra; S Bhargavi Latha; Sucharitha Yadala; Gopal Kumar Thakur (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Weed Detection Approach for Soybeans Using Fuzzy Ensemble and Image Similarity - G. V. S. Narayana; Sanjay K. Kuanar; Punyaban Patel; S. Gopal Krishna Patro; Ayodeji Olalekan Salau (Journal of Crop Health, 2026)

Association of NLRP3 (rs10754558, rs3806268, rs12137901) and ABCG2 (rs2231142) Gene Polymorphisms in Gout Susceptibility Among Asian and Caucasian Populations: A Meta-Analysis - Sharon Benita Stephen; Niranjan Gopal; R. Muthuvel; S. Waheeda; Gowtham Kumar Subbaraj (Indian Journal of Clinical Biochemistry, 2026)

Microplastics and coliforms distribution in distinctive magnetic minerals content beaches of Northwest coast of India under typical metocean conditions - Abhay B. Fulke; Gopal Krushna Swain; Harshal S. Jadhav; Shreya Bhanushali; G. Udhaba Dora; Jyotirmaya Panigrahi; Firoz Badesab (Marine Pollution Bulletin, 2026)

Greener seas: trade-offs in carbon emission reduction and fuel efficiency in Indian marine fisheries - Aparna Anil; Neha W. Qureshi; Talib Mohammad; P. S. Ananthan; Nikita Gopal (Fisheries Science, 2026)

Satellite-derived gross primary productivity estimation in hill agriculture over rice–wheat cropping systems using the vegetation photosynthesis model - Akarsh Shivhalli Gopal; Shweta Pokhariyal; N. R. Patel; R. S. Rana; R. P. Singh; Prakash Chauhan (Modeling Earth Systems and Environment, 2025)

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Trichoderma spp. as a novel pathogen for maize post-flowering stalk rot in India - J. Harish; M.K. Prasannakumar; R. Karan; Gopal Venkateshbabu; N. Vamsidharreddy; K.N. Pallavi; Swathi S. Patil; Pramesh Devanna; C. Manjunatha; H.B. Mahesh (Crop Protection, 2025)

Avoiding areas with high livestock pressure: Understanding impacts of livestock on markhor in north-western Himalayas - Riyaz Ahmad; Charudutt Mishra; Koustubh Sharma; Navinder J Singh; Gopal S. Rawat; Yash Veer Bhatnagar (Journal for Nature Conservation, 2025)

Effect of loose sand layers within dense sand on the lateral capacity of extra-extra-large monopiles - Aliasger Essakali Haiderali; Gopal S. P. Madabhushi (Marine Georesources & Geotechnology, 2025)

Assessment of climate change vulnerability of agriculture in coastal districts of India using principal component analysis and entropy-based methods - Bappa Das; Sonam Sah; K. V. Reddy; S. J. Balaji; Sujeet Desai; Gopal Mahajan; Pooja Singh; Saurav Saha; Uthappa AR; Parveen Kumar; V. K. Sehgal; Ram N. Singh; et al. (Theoretical and Applied Climatology, 2025)

Monitoring endocrine-disrupting compounds and risk assessment in the southwest coastal regions of India using black clams (Villorita cyprinoides) as an indicator - Nasreen Nazar; S. Sreejith; J. Bindu; Nikita Gopal; Niladri Sekhar Chatterjee (Marine Pollution Bulletin, 2025)

The Human Shield Hypothesis: Does Predator Avoidance of Humans Create Refuges for Prey? - Kaitlyn M. Gaynor; Eamonn I. F. Wooster; April Robin Martinig; Jennifer R. Green; Aimee Chhen; Sandra Cuadros; Ryan Gill; Gopal Khanal; Nicola Love; Rekha Marcus; C. Lauren Mills; Kwasi Wrensford; et al. (Ecology Letters, 2025)
As anthropogenic disturbance restructures ecological communities worldwide, ecologists have developed and tested hypotheses about which species “win” and “lose” in the face of human impacts. One heavily invoked paradigm is that of the human shield, which posits that predators avoid areas of human disturbance due to perceived risk from humans, and prey therefore seek refuge in these areas of perceived safety. Since its introduction in 2007, the human shield hypothesis (HSH) has gained popularity in the ecological literature, although there are more passing mentions of human shields than there are robust tests of the HSH. Here, we systematically review evidence for the HSH and evaluate how it is commonly discussed and tested. While there are several clear‐cut cases of human shields, the emergence of human shields is highly context‐dependent. By formally outlining the assumptions of the HSH, we derive predictions about what ecological and anthropogenic contexts are most likely to be conducive to human shields. Further robust studies that compete the HSH against alternative hypotheses and account for confounding factors can shed light on the role of human shields in human‐modified ecosystems and inform the conservation and management of wildlife in a changing world.

Rationally Designed Maleimide Dyes for Large Stokes Shifted Solvatochromism and Aggregation-Induced Emission - Kirankumar S. Gosavi; Aniket Patil; Gopal Wagh; Gunvant H. Sonawane; Abhishek Panigrahi; Deepak; Kaushik Pal (Journal of Fluorescence, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Incremental machine learning and genetic algorithm for optimization and dynamic aeration control in wastewater treatment plants - Celestine Monday; Mohamed S. Zaghloul; Diwakar Krishnamurthy; Gopal Achari (Journal of Water Process Engineering, 2025)

Microbial responses on upwelling signature across reversal wind pattern in tropical coastal environment off Mumbai, India - Abhay B. Fulke; Pallavi S. Salgaonkar; Gopal Krushna Swain; Komal Khade; G. Udhaba Dora (Marine Pollution Bulletin, 2024)

Estimating Soil Organic Carbon Using Sensors Mounted on Unmanned Aircraft System and Machine Learning Algorithms - Rahul Tripathi; Shiv Sundar Jena; Chinmaya Kumar Swain; Gopal Dutta; Bismay Ranjan Tripathy; Sangita Mohanty; P. C. Jena; Asit Pradhan; R. N. Sahoo; S. D. Mohapatra; A. K. Nayak (Journal of the Indian Society of Remote Sensing, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Land cover mapping of mixed classes using 2D CNN with multi-frequency SAR data - Anjana N.J. Kukunuri; Gopal S. Phartiyal; Dharmendra Singh (Advances in Space Research, 2024)

Stalk rot species diversity and molecular phylogeny associated with diseased maize in India - J. Harish; Gopal Venkateshbabu; M. K. Prasannakumar; Pramesh Devanna; H. B. Mahesh; D. C. Balasundara; S. Dharanendra Swamy; Sridhara G. Kunjeti; C. Manjunatha; M. E. Puneeth; H. C. Lohithaswa; Prashant P. Jambhulkar (World Journal of Microbiology and Biotechnology, 2024)

Photo-Catalytic Reduction of Destructive U(VI) from Uranium-Defiled Wastewater: an Overview - S. Gopal Krishna Patro; Amrutashree Hota; Ayodeji Olalekan Salau (Water, Air, & Soil Pollution, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Experimentation on triple-blended concrete with manufactured sand replaced by granulated blast furnace slag for fine aggregates - K. A. Impa; K. C. Sachin; R. Abhishek; Gopal Bharamappa Bekkeri; Kiran K. Shetty; S. R. Shashikumara (Innovative Infrastructure Solutions, 2024)
Concrete has become a versatile material by adapting itself to user needs, from pavers to skyscrapers. Escalated demand for concrete is the prime reason for the exploitation of resources and increased carbon emissions. This research focuses on reducing the environmental impact of cement manufacturing by partly replacing cement with 40% ground granulated blast furnace slag (GGBS) and 20% fly ash (FA). Waste management is also uplifted by fractional replacement of manufactured sand (M-sand) with granulated blast furnace slag (GBFS) at various intervals. Results of mechanical properties prove that this triple-blend M25 concrete with 60% GBFS and 40% M-sand as a fine aggregate would exhibit optimum mechanical properties and a maximum density of 2.58 g/cc. Tests on durability properties assure that, at the same replacement level, the percentage of weight loss due to acid attack was the lowest, with a value of 1.9, and the percentage of weight gain due to sulfate attack was as low as 0.12. The end product obtained with 40% M-sand and 60% GBFS as fine aggregates will be cost-effective and eco-friendly, making triple-blended concrete dense, durable, and sustainable and promoting waste management.

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Wound healing activities of PVA–urea composites from Ormocarpum cochinchinense - N. Aarthi; M. Muthuraj; M. Archana; V. Gopal; N. Balasubramanian; S. Rajeswari (Natural Product Research, 2024)

Low Ionosphere Density Above the Earthquake Epicentre Region of Mw 7.2, El Mayor–Cucapah Earthquake Evident from Dense CORS Data - Gopal Sharma; Karan Nayak; Rosendo Romero-Andrade; M. A. Mohammed Aslam; K. K. Sarma; S. P. Aggarwal (Journal of the Indian Society of Remote Sensing, 2024)

Removing fluoride ions from wastewater by Fe3O4 nanoparticles: Modified Rhodophytes (red algae) as biochar - Amrutashree Hota; S. Gopal Krishna Patro; Sanjaya Kumar Panda; Mohammad Amir Khan; Mohd Abul Hasan; Saiful Islam; Majed Alsubih; Nadeem A. Khan; Sasan Zahmatkesh (Journal of Water Process Engineering, 2024)

Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Gopal S. Kallure; Shubhranshu Shekhar Sahoo; Rutuja S. Kale; Vitthal T. Barvkar; Ravindar Kontham; Ashok P. Giri (Insect Biochemistry and Molecular Biology, 2024)

Extraction, characterization and the antioxidant activity of carotenoid pigment canthaxanthin from an aero-terrestrial and filamentous green microalga Trentepohlia sp. - Elumalai Sanniyasi; Rajesh Kanna Gopal; Preethy P. Raj; Kalaiselvi R.; Chandhinipriya S. (Bioresource Technology Reports, 2024)

Numerical modelling of the seismic response of gentle slopes in Southeastern Brazil - Cristian Yair Soriano Camelo; Maria Cascão Ferreira de Almeida; Marcio de Souza Soares de Almeida; Gopal S. P. Madabhushi; Brian Carlton (Marine Georesources & Geotechnology, 2024)

Performance, Combustion, and Emission analysis of diesel engine fuelled with pyrolysis oil blends and n-propyl alcohol-RSM optimization and ML modelling - K. Sunil Kumar; Raviteja Surakasi; S Gopal Krishna Patro; Nikhil Govil; M.K. Ramis; Abdul Razak; Prabhakar Sharma; Majed Alsubih; Saiful Islam; T.M.Yunus Khan; Naif Almakayeel; Sanjay Chintakindi (Journal of Cleaner Production, 2024)

Visible to near-infrared broadband electrochromic switching of π-extended viologen exhibiting highly efficient photothermal conversion - Balamurugan Gopal; Raksha Pal; Jong S. Park (Chemical Engineering Journal, 2024)

Reduced expression of chlorophyllide a oxygenase (CAO) decreases the metabolic flux for chlorophyll synthesis and downregulates photosynthesis in tobacco plants - Ajaya K. Biswal; Gopal K. Pattanayak; Kamal Ruhil; Deepika Kandoi; Sushree S. Mohanty; Sadhu Leelavati; Vanga S. Reddy; Govindjee Govindjee; Baishnab C. Tripathy (Physiology and Molecular Biology of Plants, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

A combined approach using b-value and ionospheric GPS-TEC for large earthquake precursor detection: a case study for the Colima earthquake of 7.7 Mw, Mexico - Karan Nayak; Rosendo Romero-Andrade; Gopal Sharma; Juan Luis Cabanillas Zavala; Charbeth López Urias; Manuel E. Trejo Soto; S. P. Aggarwal (Acta Geodaetica et Geophysica, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Corrigendum to addresses “Effective biocontrol of banana fusarium wilt tropical race 4 by a bacillus rhizobacteria strain with antagonistic secondary metabolites” [Rhizosphere 18 (2021) 100341] - Kavita Yadav; T. Damodaran; Kakoli Dutt; Arjun Singh; M. Muthukumar; S. Rajan; Ram Gopal; P.C. Sharma (Rhizosphere, 2023)

Liquefaction analysis of soil plugs within large diameter monopiles using numerical modelling - Carlos Español-Espinel; Stuart K. Haigh; Gopal S. P. Madabhushi (Bulletin of Earthquake Engineering, 2023)
Soil plug formation in open-ended piles due to pile driving is a widely studied phenomenon in onshore applications. The narrow diameters of traditional onshore piles ranging from 0.5 to 1.5 m facilitate plug generation during installation and transfer of enhanced confining stresses across the whole body of the soil plug. Offshore wind monopiles with larger diameters and smaller aspect ratios may not enhance confining stress within the soil plug as effectively as their onshore counterparts. Monopiles are currently the most widespread foundation in the offshore wind sector including in seismic areas. Earthquake shaking can lead to accumulation of excess pore pressure and subsequent liquefaction of the soil retained inside the plug. This research investigates the influence of monopile diameter and confining stress on the development of earthquake-induced excess pore pressure within the soil plug using fully coupled time domain Finite Element Analysis. The results presented in this paper reveal lower accumulation of earthquake-induced excess pore pressure in soil plugs subjected to confining stress. However, the influence of additional horizontal stress caused by monopile driving on the generation of excess pore pressure within the soil plug diminishes as the monopile diameter is progressively increased.

Physical modelling of the interaction between a tunnel and a building in a liquefying ground and its mitigation - Gaetano Miranda; Valeria Nappa; Emilio Bilotta; Stuart K Haigh; Gopal S P Madabhushi (Tunnelling and Underground Space Technology, 2023)

Generation of map on natural environmental background absorbed dose rate in India - Manish K. Mishra; S.K. Jha; Aditi C. Patra; D.G. Mishra; S.K. Sahoo; S.K. Sahu; Gopal P. Verma; Shashank S. Saindane; Pratip Mitra; S. Garg; Vandana Pulhani; I.V. Saradhi; et al. (Journal of Environmental Radioactivity, 2023)

Groundwater Quality Analysis and Drinkability Prediction using Artificial Intelligence - Niranjan Panigrahi; S. Gopal Krishna Patro; Raghvendra Kumar; Michael Omar; Tran Thi Ngan; Nguyen Long Giang; Bui Thi Thu; Nguyen Truong Thang (Earth Science Informatics, 2023)

Phyto-bacterial biosorption of basic fuchsine: A self-sustainable approach towards biomitigation of contaminant of emerging concern - Neetha Nirupam Jathanna; Girish Kumar Krishnamurthy; Jagdish Gopal Paithankar; Smitha Hegde; Louella Concepta Goveas; Bilachi S. Ravindranath; Mahendra Gowdru (Journal of Environmental Chemical Engineering, 2023)

Bioengineered dual fluorescent carbon nano dots from Indian long pepper leaves for multifaceted environmental and health utilities - Debadatta Mohapatra; Ravi Pratap; Vivek Pandey; Singh Shreya; Gaurav Gopal Naik; Subhash C. Mandal; Sunday O. Otimenyin; Pawan K. Dubey; Avanish S. Parmar; Alakh N. Sahu (Environmental Science and Pollution Research, 2023)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Prevalence of traditional, complementary, and alternative medicine (TCAM) among adult cancer patients in Malawi - Jacob Hill; Ryan Seguin; Agness Manda; Maria Chikasema; Olivia Vaz; Quefeng Li; Hannan Yang; Satish Gopal; Jennifer S. Smith (Cancer Causes & Control, 2022)

Ceropegia hookeri C.B. Clarke ex Hook.f. (Apocynaceae: Asclepiadoideae), an Endangered species new record for the flora of Western Himalaya, India - Kamal Kishor; Gopal S. Rawat; Sher S. Samant (Vegetos, 2022)

63 K and 50 K SNP array based high-density genetic mapping and QTL analysis for productivity and fiber quality traits in cotton - S. Anjan Gowda; Ishwarappa S. Katageri; Rajesh S. Patil; P. Sharat Kumar; Gopal J. Tiwari; Satya N. Jena; Samir V. Sawant (Euphytica, 2022)

Role of Zinc Solubilizing Bacteria in Enhancing Growth and Nutrient Accumulation in Rice Plants (Oryza sativa) Grown on Zinc (Zn) Deficient Submerged Soil - S. Prathap; S. Thiyageshwari; R. Krishnamoorthy; J. Prabhaharan; B. Vimalan; N. O. Gopal; R. Anandham (Journal of Soil Science and Plant Nutrition, 2022)

Shifts in Bacterial Community Composition and Functional Traits at Different Time Periods Post-deglaciation of Gangotri Glacier, Himalaya - Pamela Bhattacharya; Pankaj Tiwari; Gautam Talukdar; Gopal S. Rawat (Current Microbiology, 2022)

Quantifying and Modeling the Influence of Temperature on Growth and Reproductive Development of Sesame - Gurjinder S. Baath; Vijaya Gopal Kakani; Brian K. Northup; Prasanna H. Gowda; Alexandre C. Rocateli; Hardeep Singh (Journal of Plant Growth Regulation, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Preface: the central role of zooplankton in freshwaters, a special issue in honour of late Ramesh D. Gulati - S. S. S. Sarma; S. Nandini; H. J. Dumont; Brij Gopal (Aquatic Ecology, 2021)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Diversity and biopotential of Bacillus velezensis strains A6 and P42 against rice blast and bacterial blight of pomegranate - Siddulakshmi Prasanna; M. K. Prasannakumar; H. B. Mahesh; Gopal Venkatesh Babu; P. Kirnaymayee; M. E. Puneeth; Karthik S. Narayan; D. Pramesh (Archives of Microbiology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Science Alone Won’t Do It! South Africa’s Endangered Humpback Dolphins Sousa plumbea Face Complex Conservation Challenges - Stephanie Plön; Shanan Atkins; Vic Cockcroft; Danielle Conry; Sasha Dines; Simon Elwen; Enrico Gennari; Keshni Gopal; Tess Gridley; Sandra Hörbst; Bridget S. James; Gwenith Penry; et al. (Frontiers in Marine Science, 2021)
The Indian Ocean humpback dolphin ( Sousa plumbea ) is “endangered” with likely less than 500 animals remaining in South African waters. Established in 2016, the SouSA Consortium is a formalised network of scientists and conservationists to combine knowledge and research efforts, and make coordinated decisions with the aim of conserving the species. The first collaborative project collated available photo-identification data in an attempt to refine a national population estimate and investigate movements between research sites. This work was able to identify 250 uniquely marked individuals, with the population divided into the south-coast (Agulhas bioregion) and east-coast (Natal bioregion) populations. Environmental factors almost certainly play a role in the declining numbers of the species in South African waters. However, individual threats and solutions are challenging to identify as the South African marine environment is undergoing significant natural and anthropogenic changes with major shifts in the distribution and numbers of some prey, competitor and predator species. Therefore, we believe that a continued investigation of potential contributing factors and their interaction will take too long, inevitably resulting in another case of documenting extinction. With this in mind, we present the results of a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis in an effort to help us identify the next steps to take toward the conservation of humpback dolphins in South African waters. We unanimously conclude that no single cause for the rapid decline of humpback dolphins in South African waters can be identified, and that the cumulative effects of multiple stressors, which are difficult to pinpoint and mitigate, are impacting population numbers. While highlighting the need for continued research, we suggest a shift toward more action-focused conservation efforts, the first concrete steps being the development of a Conservation Management Plan with input from other stakeholders.

Artificial night light alters ecosystem services provided by biotic components - Rajesh K. Singhal; Jyoti Chauhan; Hanuman S. Jatav; Vishnu D. Rajput; Gopal S. Singh; Bandana Bose (Biologia Futura, 2021)

Modelling potentially suitable lac cultivation zones of Butea monosperma to promote livelihood security in rural India - Sharad Tiwari; Brojo Gopal Ghosh; S. N. Vaidya; Sk Mujibar Rahaman; Masjuda Khatun; Sanjoy Garai; Purabi Saikia; Amit Kumar (Vegetos, 2021)

Management of Fusarium root rot of coriander with chemical and bio‐control agents - M. S. V. Satyanarayana; K. Gopal; Ch. Ruth; S. Sadarunnisa; V. Vijaya Bhaskar (Indian Phytopathology, 2021)

Rapid genotyping of bacterial leaf blight resistant genes of rice using loop-mediated isothermal amplification assay - M. K. Prasannakumar; Buela P. Parivallal; Chennappa Manjunatha; Devanna Pramesh; Karthik S. Narayan; Gopal Venkatesh; Sahana N. Banakar; H. B. Mahesh; Ramu S. Vemanna; K. T. Rangaswamy (Molecular Biology Reports, 2021)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Making ecosystem services approach operational: Experiences from Dhauladhar Range, Western Himalaya - Anjali Uniyal; Sanjay Kr. Uniyal; Gopal S. Rawat (Ambio, 2020)

Aerobic biodegradation of high explosive hexahydro-1,3,5- trinitro-1,3,5-triazine by Janibacter cremeus isolated from contaminated soil - Anchita Kalsi; S. Mary Celin; Jai Gopal Sharma (Biotechnology Letters, 2020)

Fifty years of research on plankton ecology, biomanipulation and restoration of shallow lakes in the Netherlands: a tribute to Dr. Ramesh Datt Gulati (1935–2019) - Brij Gopal; S. S. S. Sarma; S. Nandini (Hydrobiologia, 2020)

Tuna Red Meat as a Novel Ingredient in Pet Food for Dogs - R. Yathavamoorthi; C. T. Nithin; T. R. Ananthanarayanan; Suseela Mathew; J. Bindu; R. Anandan; T. K. S. Gopal (Journal of Aquatic Food Product Technology, 2020)

Building sustainability in the Eastern Himalaya: linking evidence to action - Sandeep Tambe; Gopal S. Rawat; Nima Tashi Bhutia; Pem Norbu Sherpa; Subash Dhakal; Sarika Pradhan; Himanshu Kulkarni; M. L. Arrawatia (Environment, Development and Sustainability, 2020)

Correction to: Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Rice cultivar diversity, associated indigenous knowledge and management practices in a lowland village landscape from north-eastern India - Joylata Laishram; Krishna Gopal Saxena; K. S. Rao (Vegetos, 2020)

Multi-Functional Carbon Dots from an Ayurvedic Medicinal Plant for Cancer Cell Bioimaging Applications - Gaurav Gopal Naik; Md. Bayazeed Alam; Vivek Pandey; Debadatta Mohapatra; Pawan K. Dubey; Avanish S. Parmar; Alakh N. Sahu (Journal of Fluorescence, 2020)

Spatial patterns of plant functional types and environmental proxies of plant richness in alpine region of Western Himalaya, India - Hitendra Padalia; Aimon Bushra; Gajendra Singh; Subrata Nandy; Ishwari Datt Rai; Gopal S. Rawat (Biodiversity and Conservation, 2019)

Seismic behaviour of soft clay and its influence on the response of friction pile foundations - Thejesh Kumar Garala; Gopal S. P. Madabhushi (Bulletin of Earthquake Engineering, 2019)

Identification of Rhizosphere Bacterial Diversity with Promising Salt Tolerance, PGP Traits and Their Exploitation for Seed Germination Enhancement in Sodic Soil - T. Damodaran; V. K. Mishra; S. K. Jha; Umesh Pankaj; Garima Gupta; Ram Gopal (Agricultural Research, 2019)

Plant studies in the first Himalayan Biosphere Reserve: a review - Amit Kumar; Mansa Srivastav; Bhupendra S Adhikari; Gopal S Rawat (Journal of Mountain Science, 2019)

Investigation of infiltration rate for soil-biochar composites of water hyacinth - Phani Gopal; Sanandam Bordoloi; Raval Ratnam; Peng Lin; Weiling Cai; Poly Buragohain; Ankit Garg; S. Sreedeep (Acta Geophysica, 2019)

How global climate change and regional disturbance can expand the invasion risk? Case study of Lantana camara invasion in the Himalaya - Ninad Avinash Mungi; Nicholas C. Coops; K. Ramesh; Gopal S. Rawat (Biological Invasions, 2018)

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Economic assessment of agri-horticulture production systems on reclaimed ravine lands in Western India - V. C. Pande; R. S. Kurothe; Gopal Kumar; H. B. Singh; S. P. Tiwari (Agroforestry Systems, 2018)

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Changes in structure and function of bacterial communities during coconut leaf vermicomposting - Murali Gopal; Shrikant S. Bhute; Alka Gupta; S. R. Prabhu; George V. Thomas; William B. Whitman; Kamlesh Jangid (Antonie van Leeuwenhoek, 2017)

Fish Scales as Potential Substrate for Production of Alkaline Protease and Amino Acid Rich Aqua Hydrolyzate by Bacillus altitudinis GVC11 - N. Harikrishna; S. Mahalakshmi; K. Kiran Kumar; Gopal Reddy (Indian Journal of Microbiology, 2017)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Transcriptomic and proteomic analysis of yellow mosaic diseased soybean - Bapatla Kesava Pavan Kumar; S. Kanakala; V. G. Malathi; P. Gopal; R. Usha (Journal of Plant Biochemistry and Biotechnology, 2017)

Fermentative Properties of Proteolytic Pediococcus Strains Isolated from Salt Fermented Fish Hydrolysate Prepared Using Freshwater Fish Rohu ( Labeo rohita ) - G. S. Siddegowda; N. Bhaskar; Shubha Gopal (Journal of Aquatic Food Product Technology, 2017)

Centrifuge modelling of the seismic performance of soft buried barriers - Valeria Nappa; Emilio Bilotta; Alessandro Flora; S. P. Gopal Madabhushi (Bulletin of Earthquake Engineering, 2016)

Lecithin and PLGA-based self-assembled nanocomposite, Lecithmer: preparation, characterization, and pharmacokinetic/pharmacodynamic evaluation - Seby Elsy Varghese; Mayur K. Fariya; Gopal Singh Rajawat; Frank Steiniger; Alfred Fahr; Mangal S. Nagarsenker (Drug Delivery and Translational Research, 2016)

Comparative Evaluation of Natural Antioxidant Coating and Vacuum-Packaging Technique on Quality Characteristics of Chill Stored Giant Trevally Fillets - P. K. Binsi; C. N. Ravishankar; S. Suseela Mathew; V. P. Athira; K. B. Biji; C. G. Joshy; T. K. Srinivasa Gopal (Journal of Aquatic Food Product Technology, 2016)

Geochemical study of core sediments from Ennore Creek, North of Chennai, Tamil Nadu, India - V. Gopal; G. Kalpana; S. Nethaji; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Evaluation of total trace metal (TTMs) enrichment from estuarine sediments of Uppanar, southeast coast of India - G. Kalpana; A. Shanmugasundharam; S. Nethaji; Arya Viswam; R. Kalaivanan; V. Gopal; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Genotype–phenotype analysis of von Hippel–Lindau syndrome in fifteen Indian families - Narendranath Vikkath; Sindhu Valiyaveedan; Sheela Nampoothiri; Natasha Radhakrishnan; Gopal S. Pillai; Vasantha Nair; Ginil Kumar Pooleri; Georgie Mathew; Krishnakumar N. Menon; Prasanth S. Ariyannur; Ashok B. Pillai (Familial Cancer, 2015)

Preparation and characterization of humic acid–carbon hybrid materials as adsorbents for organic micro-pollutants - Emad K. Radwan; Hany H. Abdel Ghafar; Ahmed S. Moursy; Cooper H. Langford; Ahmed H. Bedair; Gopal Achari (Environmental Science and Pollution Research, 2015)

Sequence analysis of Indian iris yellow spot virus ambisense genome segments: evidence of interspecies RNA recombination - S. J. Gawande; V. S. Gurav; A. A. Ingle; D. P. Martin; R. Asokan; J. Gopal (Archives of Virology, 2015)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Microsatellite Markers to Determine Population Genetic Structure in the Golden Anchovy, Coilia dussumieri - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; K. K. Musammilu; V. S. Basheer; J. K. Jena (Biochemical Genetics, 2014)

Molecular phylogeny of elasmobranchs inferred from mitochondrial and nuclear markers - A. Pavan-Kumar; P. Gireesh-Babu; P. P. Suresh Babu; A. K. Jaiswar; V. Hari Krishna; K. Pani Prasasd; Aparna Chaudhari; S. G. Raje; S. K. Chakraborty; Gopal Krishna; W. S. Lakra (Molecular Biology Reports, 2014)

Increased sarcolipin expression and decreased sarco(endo)plasmic reticulum Ca2+ uptake in skeletal muscles of mouse models of Duchenne muscular dystrophy - Joel S. Schneider; Mayilvahanan Shanmugam; James Patrick Gonzalez; Henderson Lopez; Richard Gordan; Diego Fraidenraich; Gopal J. Babu (Journal of Muscle Research and Cell Motility, 2013)

Effect of Actin Polymerization Inhibitor During Oocyte Maturation on Parthenogenetic Embryo Development and Ploidy in Capra hircus - R. Ranjan; R. K. Singh; T. Yasotha; Manish Kumar; Gopal Puri; Kuldeep Kumar; Renu Singh; Sanjeev Bhure; D. Malakar; S. K. Bhanja; M. Sarkar; B. C. Das; et al. (Biochemical Genetics, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

3D-QSAR pharmacophore modeling and in silico screening of phospholipase A2α inhibitors - Shailesh V. Jain; Manjunath Ghate; Kamlendra S. Bhadoriya; Sanjaykumar B. Bari; Gopal Sugandhi; Prashant Mandwal (Medicinal Chemistry Research, 2013)

Biosorption of arsenic in drinking water by submerged plant: Hydrilla verticilata - Shubha Nigam; Krishna Gopal; Padma S. Vankar (Environmental Science and Pollution Research, 2013)

First report of an alphasatellite associated with Okra enation leaf curl virus - S. A. Chandran; R. M. Packialakshmi; K. Subhalakshmi; C. Prakash; K. Poovannan; A. Nixon Prabu; P. Gopal; R. Usha (Virus Genes, 2013)

Biosorption of arsenic from aqueous solution using dye waste - Shubha Nigam; Padma S. Vankar; Krishna Gopal (Environmental Science and Pollution Research, 2013)

Ground-based in situ measurements of near-surface aerosol mass concentration over Anantapur: Heterogeneity in source impacts - B. S. K. Reddy; K. R. Kumar; G. Balakrishnaiah; K. R. Gopal; R. R. Reddy; V. Sivakumar; S. Md. Arafath; A. P. Lingaswamy; S. Pavankumari; K. Umadevi; Y. N. Ahammed (Advances in Atmospheric Sciences, 2013)

Studies on urban drinking water quality in a tropical zone - Mohana Krishna Reddy Mudiam; S. P. Pathak; K. Gopal; R. C. Murthy (Environmental Monitoring and Assessment, 2012)

Biomass and diversity of dry alpine plant communities along altitudinal gradients in the Himalayas - Tsewang Namgail; Gopal S. Rawat; Charudutt Mishra; Sipke E. van Wieren; Herbert H. T. Prins (Journal of Plant Research, 2012)

Production and characterization of somatic hybrids between Solanum tuberosum L. and S. pinnatisectum Dun. - D. Sarkar; Jagesh K. Tiwari; Sushruti Sharma; Poonam; Sanjeev Sharma; J. Gopal; B. P. Singh; S. K. Luthra; S. K. Pandey; D. Pattanayak (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Erratum to: Sediment identification using free fall penetrometer acceleration-time histories - Gopal K. Mulukutla; Lloyd C. Huff; Jeffrey S. Melton; Kenneth C. Baldwin; Robert A. McConnaughey; Larry A. Mayer (Marine Geophysical Research, 2011)

Sediment identification using free fall penetrometer acceleration-time histories - Gopal K. Mulukutla; Lloyd C. Huff; Jeffrey S. Melton; Kenneth C. Baldwin; Larry A. Mayer (Marine Geophysical Research, 2011)

Carbon and oxygen isotopic variations in stromatolitic dolomites of Palaeoproterozoic Vempalle Formation, Cuddapah Basin, India - Gopal Chakrabarti; Debasish Shome; Subhasish Kumar; John S. Armstrong-Altrin; Alcides N. Sial (Carbonates and Evaporites, 2011)

Pseudomonas lurida M2RH3 (MTCC 9245), a psychrotolerant bacterium from the Uttarakhand Himalayas, solubilizes phosphate and promotes wheat seedling growth - Govindan Selvakumar; Piyush Joshi; Preeti Suyal; Pankaj K. Mishra; Gopal K. Joshi; Jaideep K. Bisht; Jagdish C. Bhatt; Hari S. Gupta (World Journal of Microbiology and Biotechnology, 2011)

Molecular and morphological characterization of somatic hybrids between Solanum tuberosum L. and S. etuberosum Lindl. - Jagesh K. Tiwari; Poonam; D. Sarkar; SK. Pandey; Jai Gopal; S. Raj Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Fungal isolates from natural pectic substrates for polygalacturonase and multienzyme production - K. Anuradha; P. Naga Padma; S. Venkateshwar; Gopal Reddy (Indian Journal of Microbiology, 2010)

Water quality assessment of Majhiaon block of Garwa district in Jharkhand with special focus on fluoride analysis - Kirti Avishek; Gopal Pathak; M. S. Nathawat; Usha Jha; Neeta Kumari (Environmental Monitoring and Assessment, 2010)

Plant diversity in sacred forest fragments of Western Ghats: a comparative study of four life forms - Navendu V. Page; Qamar Qureshi; Gopal S. Rawat; Cheppudira G. Kushalappa (Plant Ecology, 2010)

Genetic Diversity in Metapenaeus dobsoni using RAPD Analysis - Prem Sagar Mishra; Aparna Chaudhari; Gopal Krishna; Dilip Kumar; W. S. Lakra (Biochemical Genetics, 2009)

In Vitro Fermentation of Oat Bran Obtained by Debranning with a Mixed Culture of Human Fecal Bacteria - Gopal Kedia; José A. Vázquez; Dimitris Charalampopoulos; Severino S. Pandiella (Current Microbiology, 2009)

Land degradation mapping in the upper catchment of river Tons - Gopal Krishan; S. P. S. Kushwaha; A. Velmurugan (Journal of the Indian Society of Remote Sensing, 2009)

Isolation and identification of a new antibacterial entity from the Antarctic cyanobacterium Nostoc CCC 537 - Ravi K. Asthana; Deepali; Manoj K. Tripathi; Arunima Srivastava; Akhilesh P. Singh; Sureshwar P. Singh; Gopal Nath; Ranjana Srivastava; Brahm S. Srivastava (Journal of Applied Phycology, 2009)

A Confocal microscopic study on colony morphology and sporulation of Bacillus sp. - M. S. Mary; Judy Gopal; B. V. R. Tata; T. S. Rao; S. Vincent (World Journal of Microbiology and Biotechnology, 2008)

Bioproduction of polyhydroxyalkanoates from bacteria: a metabolic approach - Surabhi Naik; S. K. Venu Gopal; Priti Somal (World Journal of Microbiology and Biotechnology, 2008)

Metabolism of lysine-chromium complex in Saccharomyces cerevisiae - K. S. Karthikeyan; H. Polasa; K. Sivarama Sastry; Gopal Reddy (Indian Journal of Microbiology, 2008)

Size segregated aerosol mass concentration measurements over the Arabian Sea during ICARB - Vijayakumar S. Nair; K. Krishna Moorthy; S. Suresh Babu; K. Narasimhulu; L. Siva Sankara Reddy; R. Ramakrishna Reddy; K. Rama Gopal; V. Sreekanth; B. L. Madhavan; K. Niranjan (Journal of Earth System Science, 2008)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Sporulation and regeneration efficiency of phosphobacteria (Bacillus megaterium var phosphaticum) - M. Gomathy; M. Thangaraju; S. Gunasekaran; N. O. Gopal (Indian Journal of Microbiology, 2007)

Bacterial Contamination and Antibiotic Resistance in Fecal Coliforms from Glacial Water Runoff - S. P. Pathak; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2007)

Extraction of Multi-Class Pesticide Residues in Mango Fruits (Mangiferae indica L.): Application of Pesticide Residues in Monitoring of Mangoes - I. Mukherjee; S. Singh; P. K. Sharma; M. Jaya; M. Gopal; G. Kulshrsestha (Bulletin of Environmental Contamination and Toxicology, 2007)

Behavior of β-Cyfluthrin after Foliar Application on Chickpea (cicer aretinium L. ) and Pigeon Pea (cajanus cajan L.) - I. Mukherjee; M. Gopal; D. S. Mathur (Bulletin of Environmental Contamination and Toxicology, 2007)

Distribution, use pattern and prospects for conservation of medicinal shrubs in Uttaranchal State, India - Bhupendra S. Adhikari; Mani M. Babu; Prem L. Saklani; Gopal S. Rawat (Journal of Mountain Science, 2007)

Eudragit-coated pectin microspheres of 5-fluorouracil for colon targeting - Amol Paharia; Awesh K. Yadav; Gopal Rai; Sunil K. Jain; Shyam S. Pancholi; Govind P. Agrawal (AAPS PharmSciTech, 2007)

Development of Core Subset of Finger Millet Germplasm Using Geographical Origin and Data on 14 Quantitative Traits - Hari D. Upadhyaya; C. L. L. Gowda; R. P. S. Pundir; V. Gopal Reddy; Sube Singh (Genetic Resources and Crop Evolution, 2006)

Effect of Monocrotophos on Erythropoietic Activity and Hematological Parameters of the Freshwater Fish Channa punctatus (Bloch) - S. Agrahari; K. C. Pandey; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2006)

Identification of an antimicrobial entity from the cyanobacterium Fischerella sp. isolated from bark of Azadirachta indica (Neem) tree - Ravi K. Asthana; Arunima Srivastava; Akhilesh P. Singh; Deepali; Sureshwar P. Singh; Gopal Nath; Ranjana Srivastava; Brahm S. Srivastava (Journal of Applied Phycology, 2006)

In Vitro Detoxification of Pendimethalin by Two Actinomycetes spp - M. Gopal; S. K. Jha; L. Shukla; R. V. Rawat (Bulletin of Environmental Contamination and Toxicology, 2005)

Efficiency of Modified H2S Test for Detection of Faecal Contamination in Water - S. P. Pathak; K. Gopal (Environmental Monitoring and Assessment, 2005)

Distribution of heavy metals in sediment and water of river Gomti - Vivek K. Gaur; Sanjay K. Gupta; S. D. Pandey; Krishna Gopal; Virendra Misra (Environmental Monitoring and Assessment, 2005)

Public Water Sources in Rural Watersheds of Nepal?s Middle Mountains: Issues and Constraints - Juerg Merz; Gopal Nakarmi; Smita Shrestha; Bed M. Dahal; Bhawani S. Dongol; Monika Schaffner; Sangeeta Shakya; Subodh Sharma; Rolf Weingartner (Environmental Management, 2004)

Residues of Pendimethalin after Weed Control in Cabbage Crop (Brassica oleracea var L. Capitata) - S. Arora; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 2004)

Changing crop biodiversity and resource use efficiency of traditional versus introduced crops in the cold desert of the northwestern Indian Himalaya: a case of the Lahaul valley - Jagdish C. Kuniyal; Subhash C.R. Vishvakarma; Gopal S. Singh (Biodiversity and Conservation, 2004)

A rapid microwave protocol for Heck vinylation of aryl chlorides under air - Gopal K. Datta; Karl S. A. Vallin; Mats Larhed (Molecular Diversity, 2003)

The Indian summer monsoon as revealed by the NCMRWF system - P. L. S. Rao; U. C. Mohanty; P. V. S. Raju; Gopal Iyengar (Journal of Earth System Science, 2003)

Persistence and Effectiveness of Iprodione Against Alternaria blight in Mustard - I. Mukherjee; M. Gopal; S. C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2003)

The effectiveness of using a minituber crop for selection of agronomic characters in potato breeding programmes - J. Gopal; Raj Kumar; G. S. Kang (Potato Research, 2002)

Behaviour of β-Cyfluthrin and Imidacloprid in Mustard Crop: Alternative Insecticide for Aphid Control - M. Gopal; I. Mukherjee; S. Chander (Bulletin of Environmental Contamination and Toxicology, 2002)

Evaluating the Safety of β-Cyfluthrin Insecticide for Usage in Eggplant ( Solanum melongena L.) Crop - S. Sinha; M. Gopal (Bulletin of Environmental Contamination and Toxicology, 2002)

Impact of Distillery Effluent on Physiological Consequences in the Freshwater Teleost Channa punctatus - S. Kumar; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2001)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Progeny mean, heterosis and heterobeltiosis inSolanum tuberosum x tuberosum andS. tuberosum x andigena families under a short day sub-tropic environment - J. Gopal; G. S. Chahal; J. L. Minocha (Potato Research, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Deltamethrin Induced Physiological Changes in Freshwater Cat Fish Heteropneustes fossilis - S. Kumar; S. Lata; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 1999)

Microtuberization in potato ( Solanum tuberosum L.) - J. Gopal; J. L. Minocha; H. S. Dhaliwal (Plant Cell Reports, 1998)

Comparative performance of potato crops raised from microtubers induced in the dark versus microtubers induced in light - J. Gopal; J. L. Minocha; J. S. Sidhu (Potato Research, 1997)

Effect of Heavy Metals on the Blood Protein Biochemistry of the Fish CYPRINUS CARPIO AND ITS USE AS A BIO-INDICATOR OF POLLUTION STRESS - V. Gopal; S. Parvathy; P. R. Balasubramanian (Environmental Monitoring and Assessment, 1997)

The effect of t-butylated hydroxytoluene on glutathione linked detoxification mechanisms in rat - Catherine A. Partridge; Dat D. Dao; Thomas D. Hong; Gopal Misra; Dean S. Folse; Yogesh C. Awasthi (Archives of Toxicology, 1983)